Lactic acid bacteria viability and antibacterial activity of Etawa goat's synbiotic fermented milk - SAMSUL RIZAL; SUHARYONO SUHARYONO; ERDI SUROSO; ATRI MELATININGSIH; VIRDA AULIA SUYARTO (Society for Indonesian Biodiversity, 2023)
Abstract. Rizal S, Suharyono, Suroso E, Melatiningsih A, Suyarto VA. 2023. Lactic acid bacteria viability and antibacterial activity of Etawa goat's synbiotic fermented milk. Biodiversitas 24: 6440-6446. The aim of this research was to determine the effect of kepok banana peel extract and white ginger extract (Zingiber officinale Var. Amarum) on the lactic acid bacteria viability and the antibacterial activity of Etawa goat's synbiotic fermented milk. This study used two treatments and three replications. The first treatment was the concentration of kepok banana peel extract (0, 1, 2, and 3% (v/v)) and the second treatment was the concentration of white ginger extract (0, 1, 2, and 3% (v/v)). All treatments were incubated at 37°C for 48 hours. The characteristics of Etawa goat’s synbiotic fermented milk was evaluated by total lactic acid bacteria (LAB), total lactic acid, pH value, and antibacterial activity against pathogenic bacteria, Salmonella typhimurium. The data were analyzed using analysis of variance (ANOVA) and Least Significance Different (LSD) at 5%. The results showed that kepok banana peel extract had a significant effect on increasing total LAB, total lactic acid, pH value, and antibacterial activity. Meanwhile, white ginger extract had no significant effect on total LAB, total lactic acid, and pH but had a significant effect on the antibacterial activity. The addition of 3% kepok banana peel extract and 3% white ginger extract produced the best Etawa goat's synbiotic fermented milk. The best treatments produced Etawa goat’s synbiotic fermented milk with a total LAB of 9.13 Log cfu/mL, a total lactic acid of 0.82%, 3.41 pH, and antibacterial activity against Salmonella typhimurium with a 16.33 mm diameter clear zone.